Surgical management of post corrosive acid ingestion symptomatic gastric outlet obstruction: single institute experience in 81 patients - Shetty, Sushruth; Desai, Premal R.; Bhavsar, Mahendra S.; Vora, Hasmukh B.; Khiria, Laxman S.; Jillawar, Nikhil; Yadav, Ajay Kumar (International Surgery Journal, 2017)
Background: Corrosive injury resulting in gastric outlet obstruction (GOO) is fairly uncommon in world literature. We aim to study the socio-demographic variables of corrosive acid ingestion patients presenting as symptomatic GOO, along with the surgical procedure performed in these patients, post-operative complications and long term follow up data. Methods: We included all patients with clinical features of gastric outlet obstruction following acid ingestion, who were operated in our department between January 2006 and April 2017. We collected patient’s demographic data, parameters during surgery, body weight and nutritional status pre- and post-operatively, which were all derived from case records and outpatient records. Follow up data of the patient were collected when possible. Results: During the study period, 81 patients were enrolled in the study; 42 males, average age 35.76±3.53 years, 82% had suicidal intent of ingestion and 18% accidental; average follow-up period was 80.5 months. After an average period of 6 months, 94% underwent loop gastrojejunostomy. Approximately, 22% suffered complications like surgical site infections, postoperative fever, pulmonary infections and postoperative vomiting. Average follow up of 6.7 years done in 68 patients who underwent only bypass without resection, none of the patients developed any malignancy of upper gastrointestinal tract. Conclusions: Staged treatment for GOO patients was seen to be associated with good clinical outcomes and few complications. Bypass of cicatrised stomach without resection gives acceptable results.